Presbyterian reformers in Central Africa : a documentary account of the American Presbyterian Congo Mission and the human rights struggle in the Congo, 1890-1918 - Benedetto, Robert, 1950- (Studies in Christian Mission, 1996)
This volume contains 123 documents which illustrate the early history of the American Presbyterian Congo Mission and its struggle for human rights in the Congo from 1890-1918. The documents, many of which have never previously been published, are crucial to a full understanding of both the work of the Presbyterian Mission and its impact on the social, political, and religious life of the Congo. The book is divided into four parts. Part One documents the founding and early history of the Presbyterian Mission from 1890 to 1898. Part Two documents the deterioration of social conditions in the Congo under King Leopold, and the reform campaigns initiated by the American Mission in Britain and the United States. Part Three consists of documents related to the 1909 libel trial of William M. Morrison and William H. Sheppard, the principal leaders of the American Mission. Part Four documents the Mission's reaction to continuing human rights abuses, particularly religious persecution, under Belgian rule to 1918. The documents are annotated and the volume contains an introduction and an index.